University proceedings. Volga region. Natural sciences - I.V. Zatsepina (Известия высших учебных заведений. Поволжский регион: Естественные науки)
Background. Plant growth regulator epin-extra is a good substance for various crops. Thanks to this preparation, plants take root easily and simply, you can grow healthy planting material, fruits are well tied on fruit trees and do not crumble. The purpose of our research is to use the plant growth regulator epin-extra to root green cuttings of pear varieties in a greenhouse with a film shelter. Materials and methods. In the course of the work, experimental studies were conducted to study the rootability of green cuttings on pear varieties – Yakovlev's Memory (k), August dew, Seedless, Hera, Irista, Beauty Chernenko, Skorospelka from Michurinsk, Extravaganza, February souvenir, Miracle worker, Allegro, Yakovlev's Favorite, Tenderness, Pervomayskaya, Svetlyanka. The pear varieties February souvenir, Yakovlev's Memory (k), Skorospelka from Michurinsk, Extravaganza, Allegro had the greatest rootability when using the plant growth stimulator epin-extra (1.0 mg/l) for 24 hours. Without the use of a plant growth stimulant, pear varieties February souvenir, Yakovlev's Memory (k), Skorospelka from Michurinsk, Extravaganza, Allegro possessed. Results and conclusions. The greatest height of growth, the diameter of the conditional root neck, the number of roots, the length of the roots when treated with the plant growth stimulant epin-extra (1.0 mg /l) for 24 hours and without the use of a plant growth stimulant were demonstrated by the pear varieties February souvenir, Yakovlev's Memory (k), Skorospelka from Michurinsk, Extravaganza, Allegro.